Ecohidrologia aplicada ao gerenciamento de recursos hídricos no banhado do Taim - Conterato, Taiane Menezes (2022)
The Taim wetland (TW), located in southern Brazil, is an important wetland, considered a Federal Conservation Unit, which is home to animal and plant species and plays a key role in the survival and livelihood of residents in the region. Its suffers conflicts about the exploitation of existing resources and habitat preservation, largely due to the withdrawal of water for rice irrigation, the main economic activity in the region, which affects the water levels in the TW. In this thesis, hydrological, ecological analyses and ecohydrological modeling were carried out as subsidies for the management of water resources in the TW, establishing criteria for monitoring area. In the hydrological stage, a hydrological model was developed for simulations of water levels in the TW and indicators of hydrological alteration for wetlands (IHA-W) were determined inspired by the indicators of hydrological alteration developed by Richter et al. (1996). The IHAWs were divided into three groups: the basic characteristics of water levels, variability of water levels and extreme water levels. In addition, water levels were divided into 5 regimes: extremely low (EL), low (L), normal (N), high (H), and extremely high (EH). The IHA-Ws for the reference water levels in the TW were defined and simulation scenarios were established, considering changes in irrigation (no irrigation-Si and pregerminated irrigation method-Pg), substitution of rice planting for soybean (Sj scenario), and medium-term (Pc-m) and long-term (Pc-l) climate change scenarios. The Si and Sj scenarios caused changes in the hydroperiod, increased variability in water levels and reduced the permanence of the EL and L regimes. The Pg scenario maintained the TW reference hydroperiod behavior. The Pc-m and Pc-l scenarios simulated increased precipitation and air temperature, increasing variability of water levels and the permanence of the EH regime. Therefore, the TW hydroperiod behavior is associated with irrigation, so that when the months of irrigation occurrence are changed or in the absence of irrigation, the hydroperiod is affected. In the ecological stage, Habitat Suitability Index (HSI) developed in previous studies were validated for the species Z.bonariensis, S.californicus, S.giganteus, P.chihi, M.americana, C.melancoryphus, H.hydrochaeris, C.latirostris and T.dorbigni. In the ecohydrological stage, the HEC-EFM and HEC-RAS models were applied, evaluating the occurrences of water levels above or below the limits established by the HSIs. From the results, it was suggested the maintenance of water levels between 1.75m to 3.10m in the TW and the monitoring of P.chihi and S.californicus, because they are sensitive species to variations in water levels, in addition to the monitoring of the IHA-Ws, because, if the water levels suffer alterations, even if low, they may indicate possible extinction of species in the TW and should be considered for the habitat management.